'Africa has a history': an Afro-diasporic examination of Black education in Colombia and Brazil. Issue 3 (3rd July 2022) - Silva, Carolyn
ABSTRACT: In centering my analysis in the Americas, I examine the body of antiracist legislation composed of Colombia's General Law of Education, Law 70, and Brazil's federal Law 10.639/03, which formed the template for the teaching of Afrodescendant education, history, and culture in the national standard curricula. In looking at Colombia and Brazil, I interrogate the state of Afrodescendant education in the Americas as part of global trends of Black mobilization and political and educational reforms. Indeed, I argue that such educational policies resulted from the hemispheric resurgence of Black activist movements from within and without institutions of education, as well as the support of socio-political movements concerned with ethnic and racial diversity. Together, these forces converged with the multicultural movements throughout the globe, shaping the educational realities of Afrodescendant populations not only in Colombia and Brazil but also across the Atlantic.